Revisiting the Dusun Nyoir Rebellion in Narathiwat (South Thailand), April 1948 - Joll, Christopher Mark (Studia Islamika, 2021)
This article revisits the Dusun Nyoir rebellion of April 1948. My primary objective is to fill gaps missed by others whom I have learnt much from. Few familiar with the wider geography of violence in South Thailand are unaware of connections between this and the coordinated attacks on April 28 2004, which included the employment of Malay magic. This article demonstrates the importance of commitments to both conducting fieldwork in conservative rural communities and interacting with the secondary literature. The former revealed connections between Haji Mat Karae (who led the Dusun Nyoir rebellion) and Kyai Salleh active in Batu Pahat before the return of the British in 1945. Equally importantly, engaging in both ethnographic fieldwork and the relevant secondary literature brought into focus case studies of Malay rebellion having occurred during epochs of geo-political chaos throughout the Thai-Malay Peninsula, which those concerned with the political chaos caused by Thailand’s disorderly state have missed.